Pelestarian Kebudayaan Berbasis Kearifan Lokal di Era Globalisasi : Studi Kasus Kampung Adat Cirendeu - Juliansyah, Barkah; Nurhelmi, Anggita; Alfadhila, Sultan Aulia; Dikarsa, Asep Anggi; Aceng, Aceng; Supriadi, Supriadi (DAS Institute, 2024)
In the fast-paced era of globalization, preserving local cultural resilience poses a unique challenge. Kampung Adat Cireundeu in West Java is an example of a community that has successfully maintained its local wisdom amidst the currents of modernization. This research examines the strategies for cultural resilience in Kampung Adat Cireundeu and the role of the government in supporting its sustainability. The study found that cultural preservation in Kampung Adat Cireundeu begins within the family environment, building self-awareness among young generations through traditional approaches such as